Liquid phase IR-MALDI and differential mobility analysis of nano- and sub-micron particles. Issue 4 (11th January 2022) - Prüfert, C.; Villatoro, J.; Zühlke, M.; Beitz, T.; Löhmannsröben, H.-G.
Abstract : Infrared matrix-assisted desorption and ionization (IR-MALDI) enables the transfer of sub-micron particles (sMP) directly from suspensions into the gas phase and their characterization with differential mobility (DM) analysis. Abstract : Infrared matrix-assisted desorption and ionization (IR-MALDI) enables the transfer of sub-micron particles (sMP) directly from suspensions into the gas phase and their characterization with differential mobility (DM) analysis. A nanosecond laser pulse at 2940 nm induces a phase explosion of the aqueous phase, dispersing the sample into nano- and microdroplets. The particles are ejected from the aqueous phase and become charged. Using IR-MALDI on sMP of up to 500 nm in diameter made it possible to surpass the 100 nm size barrier often encountered when using nano-electrospray for ionizing supramolecular structures. Thus, the charge distribution produced by IR-MALDI could be characterized systematically in the 50–500 nm size range. Well-resolved signals for up to octuply charged particles were obtained in both polarities for different particle sizes, materials, and surface modifications spanning over four orders of magnitude in concentrations. The physicochemical characterization of the IR-MALDI process was done via a detailed analysis of the charge distribution of the emerging particles, qualitatively as well as quantitatively. The Wiedensohler charge distribution, which describes the evolution of particle charging events in the gas phase, and a Poisson-derived charge distribution, which describes the evolution of charging events in the liquid phase, were compared with one another with respect to how well they describe the experimental data. Although deviations were found in both models, the IR-MALDI charging process seems to resemble a Poisson-like charge distribution mechanism, rather than a bipolar gas phase charging one.